Exploitation promotes earlier sex change in a protandrous patellid limpet, Patella aspera Röding, 1798. Issue 10 (13th April 2017) - Martins, Gustavo M.; Borges, Carla D. G.; Vale, Maria; Ribeiro, Pedro A.; Ferraz, Rogério R.; Martins, Helen R.; Santos, Ricardo S.; Hawkins, Stephen J.
Abstract: Exploitation of organisms can prompt the reduction in the number and size of target populations consequently affecting reproductive output and replenishment. Here, we investigated the effects of exploitation on the population structure of a protandrous patellid limpet, Patella aspera, an overexploited Macaronesian endemic. Timed dives were used to collect animals across eleven islands of Macaronesia. Individuals were inspected for sex, size, and gonad stage. Using catch effort (time per person) per island coastal perimeter as a surrogate for exploitation intensity, we found that limpet abundance (CPUE) and mean size tended to decrease with exploitation intensity. When considering the sex of animals separately, the size of the largest male, but not females, decreased with exploitation. In contrast, the size of the smallest male remained relatively consistent, whereas the size of the smallest female decreased significantly with exploitation. As exploitation is mostly targeting larger individuals, results suggest that males are compensating the removal of larger females, by undergoing sex change at smaller and presumably earlier sizes. These results have wider implications for the conservation of P. aspera, as a reduction in female size will likely affect the numbers of oocytes produced, hence fecundity. Regulations promoting the protection of the larger‐sized animals should be enforced to safeguard the replenishment of the population. Abstract : We investigated the effects of exploitation on the population structure of a protandrous patellid limpet. On top of effects on limpet abundance and mean size, results suggest that males are compensating the removal of larger females, by undergoing sex change at smaller sizes. Regulations promoting the protection of the larger‐sized animals should be enforced to safeguard the replenishment of the population.